Customer satisfaction in mountain hotels within UNESCO Global Geoparks: an empirical study based on sentiment analysis of online consumer reviews - Frederico Carvalho; Ricardo F. Ramos; Nuno Fortes (Tourism & Management Studies)
The synergy between the accommodations and the untouched beauty of UNESCO’s Global Geoparks ensures an unforgettable encounter, blending comfort with adventure and relaxation with exploration. Although hotels have been previously investigated, the asymmetric results across mountain hotel customer satisfaction in UNESCO’s Global Geoparks are yet to be studied. This study aims to understand the online discourse and the reasons that satisfy a mountain hotel customer in UNESCO Global Geoparks. 5.590 online reviews were collected from 20 four and five-star mountain hotels in the Estrela UNESCO Global Geopark. Data were analysed through sentiment analysis (SA), and statistical analysis was used to acknowledge which variables influence satisfaction. We undertook a qualitative approach to understand the reasons for the identified sentiment. Results suggest that the seasonality, nationality, and travel experience influence satisfaction, and pool/spa is identified as critical for mountain hotel customers’ satisfaction. The new knowledge expands the understanding of the mountain hotel experience and the customers’ satisfaction with this specific type of hotel.